Façade of the Sitaleshwar Temple - Temples of India Project Team (Jio Institute, 2024)
The walls of the Sitaleshwar Temple have undergone renovation, resulting in the loss of much artistic work on the external wall. However, the surviving section reveals the early artistic and aesthetic traditions. The ornamentation on the jangha (wall) resembles the pillars of the antarala (vestibule or antechamber), depicting purnaghata kalasha (an auspicious motif that symbolizes abundance, growth, and prosperity) emitting long foliage and curvaceous, undulating creepers crowned with grassamukha (kirtimukha or face of glory).